Dynamics of Extreme Violence during the Indonesian National Revolution in Subang, 1945-1949 - Aji Samsudin; Ibnu Sodiq (Universitas Hamzanwadi, 2026)
This research aims to reconstruct the patterns and impacts of violence that occurred in the Subang region, particularly in the Pamanoekan and Tjiasem lands (P & T Lands), during the early period of the Indonesian War of Independence. Subang was a strategic area with vital economic infrastructure, making it a focal point of conflict between Dutch military interests and the guerrilla tactics of Indonesian fighters. Using the critical historical method, this study examines primary sources, including newspaper reports, memoirs, and letters from Dutch officers. The findings show that violence in Subang occurred in two main forms: infrastructure sabotage by Indonesian fighters and